Sosialisasi Penulisan Karya Ilmiah bagi Siswa SMA Kristen YPKM Ambon - Patty, Jusak; Binnendyk , Sophia; Hukom, Salmon James (Abdimas Indonesian Journal, 2024)
Academic literacy, particularly the ability to write scientific papers, remains challenging for students at YPKM Christian High School in Ambon. Based on observations and interviews with the principal and Indonesian language teachers, students struggle to develop ideas into scientific writing. This Community Service aims to introduce scientific writing techniques to students and teachers. The activity was conducted on May 7, 2024, involving 11th-grade students and teachers from various subjects. The implementation method included three main sessions: introduction to basic concepts and structure of scientific papers, citation techniques, writing bibliographies, and practical article analysis. The evaluation was conducted through questionnaires distributed to all participants. The evaluation results showed a positive response from participants regarding the relevance of the material to their needs, with the highest appreciation for the discussion and Q&A aspects. Technical constraints included limited time for practical sessions, an overly large number of participants in one group, and unstable internet connections. Recommendations for similar activities in the future include limiting the number of participants per session, extending the duration of practice, and simplifying technical materials. The involvement of teachers in this program opens up opportunities for ongoing mentoring in the classroom learning process.